2020
DOI: 10.1186/s12879-020-4893-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Gammapapillomavirus infections of mucosal epithelia with two broad-spectrum PCR protocols

Abstract: Background: Human papillomaviruses (HPVs) have been divided into mucosal and cutaneous types according to their primary epithelial tissue tropism. However, recent studies showed the presence of several cutaneous types in mucosal lesions and healthy mucosa from different anatomical sites. Methods: Here, the HPV prevalence and type-specific distribution were assessed in a variety of mucosal samples from 435 individuals using a combination of two established broad-spectrum primer systems: Gamma-PV PCR and CUT PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
2
7
2
Order By: Relevance
“…In this study, we analyzed the presence of a broad spectrum of HPV types in anal swabs from HIV-negative and HIV-positive MSM and HIV-negative MSW. In agreement with previous studies, [20][21][22][23] our results revealed the presence of a large number of alpha, beta, and gamma types in all groups, further supporting the concept that beta and gamma HPV types have the ability to infect both cutaneous and mucosal epithelia. Hampras et al reported that HPV types of the beta-3 species were more likely to infect the anal mucosa compared with other anatomical sites, such as oral mucosa or skin epithelia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we analyzed the presence of a broad spectrum of HPV types in anal swabs from HIV-negative and HIV-positive MSM and HIV-negative MSW. In agreement with previous studies, [20][21][22][23] our results revealed the presence of a large number of alpha, beta, and gamma types in all groups, further supporting the concept that beta and gamma HPV types have the ability to infect both cutaneous and mucosal epithelia. Hampras et al reported that HPV types of the beta-3 species were more likely to infect the anal mucosa compared with other anatomical sites, such as oral mucosa or skin epithelia.…”
Section: Discussionsupporting
confidence: 92%
“…3 Moreover, Bolatti et al reported that gamma PVs may also display dual tissue tropism, being highly prevalent in anal mucosa. 21 Our data show that the abundance of the specific HPV genera appears to differ in the three groups of men. Indeed, alpha HPV types were more abundantly detected in MSM than in MSW.…”
Section: Discussionmentioning
confidence: 62%
“…Oral infection by gamma HPVs appears to be less common, with a prevalence ranging from 3% to 11% [ 5 , 7 ]. A recent study confirmed the presence of these genotypes in oral swabs using broad-spectrum primer systems [ 9 ]. Although frequency of HPV oral infection in this study was low, especially compared to other mucosal sites, and alpha HPVs were the most frequent types detected in oral swabs, beta and gamma HPVs were also found.…”
Section: Introductionmentioning
confidence: 87%
“…Gamma-PVs have an extremely broad tissue tropism, infecting both cutaneous as well as mucosal and mucocutaneous epithelium, and have so far been identified in various clinical samples, including benign and malignant cutaneous neoplasms, and clinically normal skin, the oral cavity, the nasopharnx, and the anogenital area (penis, cervix, and anal canal) [7,16,26,33,34]. Similarly, the presence of the phylogenetically closest HPV179 relatives (HPV135 and HPV146) has been detected in several samples from the oral and nasal cavities, vaginal mucosa, anogenital warts, and histologically normal skin [4,6,12,13,15,27,Chen et al unpublished data].…”
Section: Discussionmentioning
confidence: 99%
“…Even though HPVs are etiologically associated with the development of several benign and malignant neoplasms of the skin and mucosa, the majority of HPV infections are transient and/ or do not cause any apparent lesions or disease [1,3]. Accordingly, Gamma-PVs have frequently been detected in histologically normal skin [4][5][6][7][8][9][10] in several mucosal anatomical sites, including oral, nasal, and cervical mucosa [11][12][13][14], and in the mucocutaneous epithelium of the penis and anal canal [15,16]. In addition, their presence has also been demonstrated in Alpha-PV-negative anogenital warts [17,18] and cervical intraepithelial lesions [11,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%